Factores que influyen en la adherencia al tratamiento de pacientes hipertensos que acuden al Hospital de Motupe. - León Vanegas, Paola Gabriela (2016)
The treatment adherence and the factors that influences it, had been a relevant theme, and a challenge to find a method which allows to improve the aspects that limits patients to accomplish the treatment. The objetives of this investigation were know the percentage of treatment adherence and also the principal factors which affects it. This was a descriptive, transversal and quantitative research, the partakers were selected from The Hypertension Club of “Hospital de Motupe”, with a sample of 50 patients. Applying Morisky Green Test and an out previously inquest were obtained these results: the 64% (n=34) weren´t adherents to the treatment, whitin the relationated factors, the 96% (n=48) manifested interest to keep healthy, and the totality 100% didn’t express any inconvenience with medication. Concluding, to accomplish a treatment includes some aspects that should interact correctly to get an optimun outcome. Keywords: Hypertension, adherence, relationated factors